Thermoregulation and Hydration in Female American Football Players During Practices. Issue 9 (September 2021) - Lopez, Rebecca M.; Ashley, Candi D.; Zinder, Steven M.; Tritsch, Amanda J.
Abstract : Abstract: Lopez, RM, Ashley, CD, Zinder, SM, and Tritsch, AJ. Thermoregulation and hydration in female American football players during practices. J Strength Cond Res 35(9): 2552–2557, 2021—Little is known about hydration practices and thermoregulation in female tackle football players. The purpose of the study was to examine the thermoregulatory and hydration responses of female professional American football players. Fifteen females from the same tackle football team volunteered for this observational field study. Each subject was observed for 4 practices for the following measures: gastrointestinal temperature (TGI ), maximum TGI, heart rate (HR), maximum HR (HRmax), fluid consumption, sweat rate, percent body mass loss (%BML), urine specific gravity (USG ), urine color (Ucol ), perceptual measures of thirst, thermal sensations, and rating of perceived exertion (RPE). Descriptive data (mean ± SD ) were calculated for all measures. Main measures were analyzed using a repeated-measures analysis of variance. Trials took place during evening practices. Average TGI during practices was 38.0 ± 0.3° C while maximum TGI was 38.4 ± 0.3° C ( n = 14). Average practice HR was 118 ± 11 b·min −1, while HRmax was 148 ± 13 b·min −1 . Subjects arrived at practices with Ucol of 3 ± 1 and USG of 1.018 ± 0.007. Postpractice USG (1.022 ± 0.007) was significantly higher than prepractice across all days ( p < 0.001). The average sweat rate across 4 practices was 0.6 ml·h −1 . Average %BML was 0.3 ± 0.4%. Thirst and thermal sensations were moderate (4 ± 1 and 5 ± 1, respectively), while RPE was 11 ± 1. Female football players tended to have similar physiological responses to males. Although subjects seemed to adequately match their sweat losses with fluid consumed during practice, there was considerable variability in hydration indices and hydration habits, with some subjects experiencing hypohydration and others overestimating their fluid needs. Those working with this population should emphasize the need for hydration education and establish individualized hydration regimens.